(untitled) (Web of Teachers: Inderscience Research, 2025)
Translational thinking is a unique and essential cognitive phenomenon that distinguishes professional translators from those who simply know two or more languages. It is based on the ability not only to understand the meaning of words and sentences in the source language, but also to reconstruct, interpret, and deliver them in the target language in a way that maintains the original sense, intention, and style. The complexity of this process requires certain mental abilities and skills, including memory retention, rapid association, conceptual mapping, anticipation, and flexibility in thinking. One of the most effective tools for forming and developing translational thinking in future translators is mnemonics.